Leveraging the Anuj transform: A novel approach to modeling population dynamics in interdisciplinary sciences - Hilmi, Hozan; Jalil, Shabaz; Rahman, Hiwa Hussein; Faraj, Bawar Mohammed (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
This study introduces the Anuj transform as an innovative tool for addressing population growth and decay problems. By applying the Anuj transform, we demonstrate its efficacy and practical value in solving these complex issues. The paper presents several applications that highlight the transformative potential of the Anuj transform in modeling population dynamics. The results underscore the utility of this method, providing clear solutions without extensive calculations.